Peningkatan Kapasitas Manajerial dan Digitalisasi Usaha Bagi Pelaku UMKM di Era Ekonomi Digital - Jannati Tangngisalu; Muh.Akob; Marwah Yusuf; Loade Sumail; Hasyim Mokhtar; Djamila Saleh (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity was carried out to enhance the managerial capacity and digital competence of Micro, Small, and Medium Enterprises (MSMEs) in Sunggu Manai Village, Patalassang District, Gowa Regency. In the digital economy era, MSME actors must adapt to technological changes and manage their businesses professionally to remain competitive. The activity employed a participatory and applicative approach involving training in business management, digital marketing, and application-based financial recording. The results showed a significant increase in participants’ knowledge and skills, particularly in business planning, financial management, and the use of social media and online marketplaces for product promotion. About 80% of participants successfully created digital business accounts and started marketing their products online. The program also fostered awareness of the importance of digital transformation and collaboration among MSME actors. Therefore, integrating managerial capacity building with business digitalization proved effective in enhancing the competitiveness and sustainability of MSMEs in rural areas.